MITOS DAN KEKUASAAN STUDI KASUS HEGEMONI NGALAP BERKAH GUNUNG KEMUKUS TERHADAP PENCARIAN KEKUASAAN - Sari, Indah Ambar; Azhar, Muhammad Ali; Erviantono, Tedi (Jurnal Nawala Politika, 2016)
ABSTRACT This study was conducted to determine how Ngalap Berkah Ritual  affect the ruling elite in finding and maintaining power. Ngalap Berkah Ritual is a ritual performed by kejawen Kemukus Mountains and surrounding communities. Pilgrims perform the ritual on Friday evenings and Friday Pon. Rituals performed in the tomb of Prince Samudro, pilgrims perform the ritual with the aim to seek blessings. This study uses qualitative research with the primary data source, the data obtained from the experts, in this study is the caretaker of the tomb of Prince Samudro. The technique of collecting data through observation, depth interviews and documentation. Then the data were analyzed descriptively qualitative. Using the theory of myth revealed by Barthes and is supported by the theory of Foucault's theory of hegemony and Theory Simotika. This study resulted in the following findings, namely the influence Ngalap Berkah Ritual of the ruling elite in finding and maintaining power. Caretaker searches hegemonic power by using symbols in doing Ngalap Berkah Ritual. Caretaker in control in Ngalap Berkah Ritual  ruling leads to successful candidates. Most perpetrators of rituals that come to Mount Kemukus successful, it can be seen from the celebration of the success of power-seekers who come to Mount Kemukus. Authors analyzed that the influence of hegemony Caretaker Mount Kemukus greatly influences the success of search power of the ruling elite. Keywords : Ritual, Ngalap Berkah Politics, Power